PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MODEL CONNECTING ORGANIZING REFLECTING EXTENDING BERBASIS KONTEKSTUAL PADA MATERI SPLDV - Brilyan Amry Siregar; Maimunah Maimunah; Nahor Murani Hutapea (Universitas Pekalongan, 2021)
The goal of learning mathematics in the 2013 curriculum require students to be able to use mathematical reasoning skills in solving problems. The fact in the field is that Junior High School number 21 Pekanbaru shows that student’s mathematical reasoning abilities are still in the low category. One of the causes of the low mathematical reasoning ability of students, the learning process carried out by the teacher, the process is contained in a device that has not been able to facilitate students 'mathematical reasoning abilities and the questions given to students are not related to students' daily lives. or not contextual. This study aims to produce a mathematics learning device design that is able to facilitate students' mathematical reasoning abilities in the SPLDV material. This research is a development research, using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The analysis was carried out in the form of performance and needs analysis, curriculum analysis, and analysis of learning device needs. At the design stage, designing mathematics learning tools using the contextual-based Connecting Organizing Reflecting Extending (CORE) model to facilitate students' mathematical reasoning abilities on SPLDV material, and in the development stage, learning tools that have been designed are validated by the validator team. The results of the data analysis of the validation of learning tools for the syllabus obtained a percentage of 93.75% with a very valid category, Learning Implementation Plan obtained a percentage of 93.45% with a very valid category, Student Worksheet obtained a percentage of 91.18% with a very valid category, Math reasoning ability test questions obtained a percentage of 90% with a very valid category.